2018
DOI: 10.1103/physrevphyseducres.14.010145
|View full text |Cite
|
Sign up to set email alerts
|

Developing the use of visual representations to explain basic astronomy phenomena

Abstract: This paper is part of the Focused Collection on Astronomy Education Research.] Several decades of research have contributed to our understanding of students' reasoning about astronomical phenomena. Some authors have pointed out the difficulty in reading and interpreting images used in school textbooks as factors that may justify the persistence of misconceptions. However, only a few studies have investigated to what extent usual textbook images influence students' understanding of such phenomena. This study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 121 publications
2
11
0
Order By: Relevance
“…Furthermore, the traditional hands-on activity for teaching Moon phases (described below) is susceptible to various real-world inaccuracies, such as creating eclipses every month or rotating or orbiting the wrong way. Research has also found that explanatory features of traditional descriptions and images can interfere with student understanding [51,52], motivating the need for authentic real-world visualizations over abstracted ones.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the traditional hands-on activity for teaching Moon phases (described below) is susceptible to various real-world inaccuracies, such as creating eclipses every month or rotating or orbiting the wrong way. Research has also found that explanatory features of traditional descriptions and images can interfere with student understanding [51,52], motivating the need for authentic real-world visualizations over abstracted ones.…”
Section: Methodsmentioning
confidence: 99%
“…Similar to earlier studies [14,15,17,18] , the results ofthe pilot test reveal that the test items on the apparent motion of the Sun are in general answered better than items on the apparent motion of stars. While prior studies [3,9,37,[55][56][57] about apparent celestial motions are mostly limited to the Sun or the Moon and in few cases to certain elements ofthe Sun's path and startrail (e.g., culmination height), the AM:oSS test allows to examine in more detail and more systematically which elements of the apparent motion of Sun and stars students really understand. By the symmetry between Sun questions and star questions, we are able to compare students' understanding of bath apparent motions.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is always revised based on the curriculum, the book content does not offer much motivation and also exercises that emphasize the use of plural representations [11]. Students have difficulty in reading and interpreting images used in textbooks [12] [13].…”
Section: Introductionmentioning
confidence: 99%